SOLID GEOMETRY LEARNING: STUDENT ERRORS IN SOLVING SOLID GEOMETRY PROBLEMS AT UNIVERSITY LEVEL - Mega Eriska Rosaria Purnomo (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2017)
The purposes of this research were to describe student errors types in solving solid geometry problems based on mathematics skills and to know the causes of student errors happened. The major mathematics skills consisted of number fact, arithmetics, information, language, visual spatial skill. This research was qualitative. Data collection techniques were done by test and interview. Respondents were 6 from 39 mathematics education students academic year of 2016/2017 in Universitas Muhammadiyah Surakarta that consisted of each 2 students in high, middle, low level respectively. This grouping were conducted based on the test results. Every respondent was interviewed about their answer of the test. The results of this research indicated that students in high level did errors on number fact and visual spatial skill. Students in middle level did errors on five type of mathematics skills. Students in low level did errors on four type of mathematics skills except arithmetics skill